Doing second language learning in the wild - Abdullah, Nur Nabilah; Sahar, Rafidah (2018)
The focus of this study is to investigate what do international students do ‘in the wild’, that is, in a mundane, everyday, out-of-classroom second language talk. In face-to-face interactions, spoken language involves not only verbal but also a mutual collaboration with other non-linguistics resources, such as gaze, gestures and bodily behaviour (Goodwin, 1981). This study aims to add to the growing body of second language (L2) research which goes ‘beyond the language classroom’, outside educational settings (Firth and Wagner, 1997; Wagner, 2004) particularly among L2 speakers who do not share the first language. The data for this study consists of casual conversation among international university students having dinner at a cafe which is video-recorded. Using conversation analysis or sometimes referred to as ‘CA-SLA’ (Kasper and Wagner, 2011), this study aims to explore how participants with different language background exploit language and other non-linguistic resources in second language talk outside of educational settings. The findings from the investigation suggest that talk, gaze and gestures as coordinated interactional resources in creating opportunities in L2 learning. The learning sequences in the L2 interaction is framed around repair activities and word searches. By analysing the repair and word search sequences, we demonstrate how participants draw on language and non-linguistic resources for understanding (Seo, 2011) and opportunity for L2 learning can take place outside a classroom environment (Firth and Wagner, 1997).